Cities in the 21st century: A view from the developing world - David Castells-Quintana; Paula Herrera (REGION, 2019)
In this (introductory) paper, we present i) some basic figures about the rise of cities in the developing world, and ii) the four papers of this special issue. This paper and the other four papers in the issue intend to bring the reality of cities of the developing world in the 21st century to the frontline, hoping to motivate further and much needed research.
Keywords: O1; O4; R1; 330; Cities; urbanisation; developing countries